2019
DOI: 10.1038/s41598-019-40281-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Visual Attention Allocation

Abstract: We often temporally prepare our attention for an upcoming event such as a starter pistol. In such cases, our attention should be properly allocated around the expected moment of the event to process relevant sensory input efficiently. In this study, we examined the dynamic changes of attention levels near the expected moment by measuring contrast sensitivity to a target that was temporally cued by a five-second countdown. We found that the overall attention level decreased rapidly after the expected moment, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…TVA has been adapted to model a constant level of expectation across time 80 , 81 , but not attention to specific time points. Second, our model distinguishes between voluntary and involuntary attention, a distinction that is supported by the spatial attention literature 35 , 82 , 83 and has been reported for temporal attention 78 , 84 86 . Third, in previous models 17 , 77 , the role of attention is to control the encoding of sensory signals into working memory.…”
Section: Discussionsupporting
confidence: 68%
“…TVA has been adapted to model a constant level of expectation across time 80 , 81 , but not attention to specific time points. Second, our model distinguishes between voluntary and involuntary attention, a distinction that is supported by the spatial attention literature 35 , 82 , 83 and has been reported for temporal attention 78 , 84 86 . Third, in previous models 17 , 77 , the role of attention is to control the encoding of sensory signals into working memory.…”
Section: Discussionsupporting
confidence: 68%
“…TVA has been adapted to model a constant level of expectation across time 76,77 , but not attention to specific time points. Second, our model distinguishes between voluntary and involuntary attention, a distinction that is supported by the spatial attention literature 35,78,79 and has been reported for temporal attention 74,[80][81][82] . Third, in previous models 17,73 , the role of attention is to control the encoding of sensory signals into working memory.…”
Section: Relation To Other Attention Models Concerned With Dynamicssupporting
confidence: 68%
“…Many studies have demonstrated that pain directs attention towards the location of its presentation (Van Damme et al, 2007Van Damme & Legrain, 2012). In addition to spatial location, temporal features are important aspects of attention (Coull & Nobre, 1998;Moon et al, 2019), but temporal attentional interruption by pain has been less well researched than its spatial counterpart. Van Ryckeghem et al (2012) found that even after the offset of a pain stimulus, pain interferes with performance on a subsequent task.…”
Section: Introductionmentioning
confidence: 99%